The Association between Resting Metabolic Rate (RMR), Respiratory Quotient (RQ) and Dietary Energy Density (DED) in overweight and obese women: Resting Metabolic Rate, Respiratory Quotient and Dietary Energy Density - Rasaei, Niloufar; Sajjadi, Seyedeh Forough; Mirzababaei, Atieh; Pooyan, Sara; Rashidbeygi, Elaheh; Yekaninejad, Mir Saeed; Imani, Hossein; Mirzaei, Khadije (Progress in Nutrition, 2020)
Aim: Dietary Energy Density (DED) defined as the energy content of foods (kJ or kcal) per unit weight of foods (g) that has an important effect in the regulation of energy intake, weight reduction, weight maintenance and waist circumference but its function in resting metabolic rate (RMR) is less understood. Therefore, we wanted to investigate the association between resting metabolic rate (RMR), respiratory quotient (RQ) and DED in overweight and obese women. Methods: A total of 301 overweight and obese women were included in the current comparative cross-sectional study. Body composition was measured using body composition analyzer. RMR was measured by means of indirect calorimetry. The usual food intake of people over the past year evaluated through the use of a semi-quantitative food frequency questionnaire. We calculate ED from food only as energy (kcal) and it was divided by the total weight of the food (g) excluding nonenergetic beverages. Results: Between low and high energy density of diets there is statistically significant difference in age, carbon dioxide uptake (VCO2), RMR/Kg body weight (RMR/Kg), RMR/body surface area (RMR/BSA) (P > 0.0001), RMR and RQ (P = 0.01). Furthermore, there is a significant relationship between the DED and RMR/Kg body weight (P > 0.0001) and finally in the regression model after adjusted for age, fat free mass and physical activity, the association of DED and RMR/Kg body weight was still significance (p